Strategi Pemasaran Ekspor Jeruk Siam di PT X - Khairunnisa, Khairunnisa; Relawati, Rahayu; Amir, Nur Ocvanny (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Export activities require the best possible marketing strategy so that the orange commodities offered are able to compete, gain profits and protect the company from competitors. This research aims to determine the company's internal and external factors as well as appropriate export marketing strategies. The research location is in Pontianak, West Kalimantan. The analysis used is SWOT equipped with qualitative descriptive. The biggest strength is that the company has an extensive network with a score of 1.00 and the biggest weakness is the lack of production facilities with a score of 1.00. The greatest opportunity is to have a definite market with a score of 0.9 and the greatest threat to the quality of Siamese oranges with a score of 1.00. The results of the research show that the company is in quadrant I, namely SO (Strength - Opportunity) where strengths are greater than weaknesses and opportunities are greater than threats with a point position of (0,66; 0,82) so that the appropriate strategy is an aggressive strategy, namely utilizing strengths. and opportunities to overcome weaknesses and threats. This position benefits the company because it has great strengths and opportunities